Math, asked by Rithanya39, 10 months ago

be first fast correct to be a brainliest answer✌✌✌✌​

Attachments:

Answers

Answered by MissAnteMeridiem
1

Answer:

0

Step-by-step explanation:

2 \times \frac{5}{6}  - (4 \times \frac{1}{3}  -  \frac{3}{2} ) =  \frac{17}{6}  - ( \frac{13}{3}  -  \frac{3}{2} ) =  \frac{17}{6}  - ( \frac{13 \times 2}{3 \times 2}  -  \frac{3 \times 3}{2 \times 3} ) =  \frac{17}{6}  - ( \frac{26}{6}  -  \frac{9}{6} ) =  \frac{17}{6}  -  \frac{17}{6}  = 0

Similar questions